As Time Goes By: Event File Decay Does Not Unleash Inhibition of Return - Lars-Michael Schöpper; Christian Frings (Journal of Cognition)
Inhibition of return (IOR) refers to a location repetition cost typically observed when signaling the detection of or localizing sequentially presented stimuli repeating or changing their location. In discrimination tasks, however, IOR is often reduced or even absent; here, effects of binding and retrieval are thought to take place. Information is bound into an event file, which upon feature repetition causes retrieval, leading to partial repetition costs. It is assumed that the presence of retrieval-based effects masks the observation of IOR. Yet, some evidence suggests that long intervals between stimuli can lead to IOR in tasks in which usually mostly binding effects are observed. We hypothesized that with an increasing interval between prime response and probe onset (response stimulus interval, RSI), event files will decay and decreasingly mask IOR. In turn, IOR should be strongest at longest intervals. In the current study, participants discriminated the color of stimuli repeating or changing their location. Crucially, we varied the RSI from 500 ms to 3000 ms, trial-wise (Experiment 1) and block-wise (Experiment 2). We observed overall binding effects that were reduced with increasing RSI; these effects were slightly stronger when presented block-wise. IOR was overall absent (Experiment 1) or weak (Experiment 2) and did not emerge with increasing RSI. While event file decay took place, it did not unleash IOR. Rather, these results suggest that retrieval-based effects do not simply mask but overwrite IOR when manually responding. The observations of IOR with long intervals are discussed in the context of overall fast responding.